Needs assessment report on bureaux of standards in Antigua and Barbuda, Grenada, St. Lucia and Montserrat within the CS/CDB project Enhancing Standards Management Capabilities in the OECS Countries - Rhynd, Dudley B. ([CARICOM Secretariat] [Georgetown]GY, 2000)
Deals with the examination of the standards bodies in the OECS countries, viz Antigua and Barbuda, Grenada and St. Lucia, and a needs assessment of all the agencies and groups involved in standards management, quality control, manufacturing and consumer protection.